2015
DOI: 10.1074/jbc.m115.686352
|View full text |Cite
|
Sign up to set email alerts
|

SR4 Uncouples Mitochondrial Oxidative Phosphorylation, Modulates AMP-dependent Kinase (AMPK)-Mammalian Target of Rapamycin (mTOR) Signaling, and Inhibits Proliferation of HepG2 Hepatocarcinoma Cells

Abstract: Mitochondrial oxidative phosphorylation produces most of the energy in aerobic cells by coupling respiration to the production of ATP. Mitochondrial uncouplers, which reduce the proton gradient across the mitochondrial inner membrane, create a futile cycle of nutrient oxidation without generating ATP. Regulation of mitochondrial dysfunction and associated cellular bioenergetics has been recently identified as a promising target for anticancer therapy. Here, we show that SR4 is a novel mitochondrial uncoupler t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 65 publications
(75 reference statements)
3
34
0
Order By: Relevance
“…A variety of studies have reported that AMPK regulates cell proliferation and apoptosis via multiple signaling pathways, such as phosphorylation and subsequent stabilization of tumor suppressor p53, upregulation of cyclin-dependent kinase inhibitors, and downregulation of the mammalian target of rapamycin complex-1 activity (7,11). In particular, it has been demonstrated that activation of AMPK is responsible for inducing apoptosis via the mitochondrial pathway (12,13). However, AMPK is also known to play a protective role in cancer cells under metabolic stressed conditions by maintenance of energy homeostasis and modulation of autophagy, making the influence of AMPK on cancer progression controversial (14,15).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of studies have reported that AMPK regulates cell proliferation and apoptosis via multiple signaling pathways, such as phosphorylation and subsequent stabilization of tumor suppressor p53, upregulation of cyclin-dependent kinase inhibitors, and downregulation of the mammalian target of rapamycin complex-1 activity (7,11). In particular, it has been demonstrated that activation of AMPK is responsible for inducing apoptosis via the mitochondrial pathway (12,13). However, AMPK is also known to play a protective role in cancer cells under metabolic stressed conditions by maintenance of energy homeostasis and modulation of autophagy, making the influence of AMPK on cancer progression controversial (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…When the cellular ATP level drops, AMPK is activated to inhibit mTOR signaling, leading to attenuation of protein synthesis (12,42). Because the mitochondrial electron transfer chain is the major source of ATP production, mitochondrial dysfunction can drive reduction of ATP synthase, which results in activation of AMPK.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial uncouplers can reduce cellular ATP levels and activate AMPK (Soltoff, 2004;Eskiocak et al, 2014;Figarola et al, 2015). We examined the effects of CCCP on cellular ATP levels and the ADP/ATP ratio in vascular smooth muscle cells (A10).…”
Section: Cccp Activates Ampk In Vascular Smooth Muscle Cells and Rat mentioning
confidence: 99%
“…This nonproductive energy leak, termed “mitochondrial uncoupling,” plays an important role in reprogramming cancer cell metabolism. Therefore, in cancer cells, regulation of mitochondrial dysfunction and associated cellular bioenergetics shows promise as a target for chemotherapeutic drug development [ 16 ].…”
Section: Introductionmentioning
confidence: 99%